On Optimal Development in a Multi-Sectoral Economy: the Discounted Case - Sutherland, W. R. S. (Review of Economic Studies, 1970)
Journal Article On Optimal Development in a Multi-Sectoral Economy: the Discounted Case Get access W. R. S. Sutherland W. R. S. Sutherland University of Toronto Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 4, October 1970, Pages 585–589, https://doi.org/10.2307/2296487 Published: 01 October 1970 Article history Received: 01 May 1969 Revision received: 01 January 1970 Published: 01 October 1970